URGENSI PENERAPAN INSTRUKSI PRESIDEN NOMOR 2 TAHUN 2022 PADA PELAKSANAAN PENGADAAN BARANG/JASA PEMERINTAH - Satrya Surya Pratama (Jurnal Komunikasi Hukum, 2022)
The Covid-19 pandemic that has hit the world since 2019 has had many impacts on various sectors, one of which is on the world economic growth and development sector, including in Indonesia. Various efforts to overcome the pandemic have been carried out to prevent the spread of Covid-19, one of which is the recommendation to stay at home which has an impact on the number of public places that are closed and has resulted in many local business actors experiencing a decrease in income and even closing their businesses. Due to these conditions, the government issued Presidential Instruction Number 2 of 2022. The purpose of this study is to find out and analyze the urgency of implementing Presidential Instruction Number 2 of 2022 on the implementation of Government Goods/Services Procurement. Primary Data is obtained through field studies, while Secondary Data is obtained through literature studies. The analysis method used is the Empirical Juridical Data Analysis Method. The results of this study show that if the presidential instruction is carried out properly by all parties, it can certainly make a positive contribution to the decline in the income of local business actors, and can increase the competitiveness of local domestic products. This implementation can bring the country's economic development in a better direction after being affected by the prolonged Covid-19 pandemic.